Reasons for real appreciation in Central Europe - Michael Brandmeier (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2006)
The real economic effects of the considerably high appreciation in Central European Economies (CEE) are controversially disputed in the eve of the European Monetary Union (EMU) entry of several CEE economies. The Balassa-Samuelson-effect was made responsible for the expectation of higher inflation rates in CEE than in the EMU in the next years. Higher inflation rates will deteriorate the price competitiveness of the export sectors in the CEE countries because of real appreciation. This paper focuses on the effects of labour productivity differences in several industrial and service sectors on the consumer prices. Labour productivity changes are affected by the technology impact on labour demand and by the relative wage increases following from tensions of regional labour markets because of rising prices and skilled labour shortage. Real appreciation is determined by labour productivity differences and by capital good imports. We conclude that the negative coherence between real appreciation and the endangered price competitiveness of the export sectors in CEE has to be taken into account, unless the negative experience of loss of competitiveness because of sudden real appreciation in Eastern Germany will take place on a large scale in the eastern part of the enlarged euro area.
Keywords: E31; F33; F41; 330; European Monetary Union; inflation differences; Balassa-Samuelson-effect; Central and Eastern Europe